Evaluation of Depression and its Related Factors Among Female Students in Fasa, Iran - Modarresi, Farzaneh; Nikouee, Farhood; Ansari, Amir; Rezaee, Mophsen (International Clinical Neuroscience Journal, 2017)
Background: We aimed to determine frequency of depression among female adolescent students and its related factors in Fasa, Iran. Methods: In a cross-sectional study, female high school students were evaluated. Depression, mental disorder and family’s relative peace were measured using standard scales. Results: A total of 516 students were evaluated in which 157 (30.4%) students did not suffer any type of depression. The mean depression score of students had significant relationship with history of an addicted family member (P < 0.001), family relative peace (P < 0.001), history of any mental-psychological disorder in family (P < 0.001) and parents’ educational level (P = 0.03). Conclusion: The prevalence of depression was high in female students and was associated with variables such as drug-addicted family member, relative peace and history of mental-psychological disorders in the family.